Fatal Listeria monocytogenes septicemia and meningitis complicated by Candida glabrata fungemia: a case report. (2nd December 2022) - Grima, Pierfrancesco; Urciuoli, Caterina; Simone, Giuseppe; Palazzo, Anna Gloria; Nuzzo, Milva; Quarta, Maurizio; Carraturo, Immacolata; Maci, Anna Maria; Marinaci, Salvatore; Portaccio, Gerolamo; Guido, Marcello; Zizza, Antonella; et al.
Abstract: Listeria monocytogenes is a Gram-positive bacteria and etiological agent of listeriosis. It has the ability to colonize the intestinal lumen and cross the intestinal, blood–brain, and placental barriers, leading to invasive listeriosis responsible for septicemia and meningitis in subjects at risk such as patients with diabetes mellitus, the elderly, and immunocompromised individuals and, for maternal-neonatal infection in pregnant women. We report a rare case of L. monocytogenes septicemia and meningitis complicated by Candida glabrata fungemia on a patient with a history of type 2 diabetes mellitus, hypothyroidism, hypertension, chronic kidney failure, chronic ischemic vascular encephalopathy, and atrial fibrillation. Although adequate therapy was rapidly started with an initial partial clinical improvement, the patient suddenly experienced clinical worsening concomitantly with Candida septicemia resulting in a fatal outcome. To our knowledge, this is the first described case of an invasive L. monocytogenes infection complicated by Candida sepsis. We hypothesize that concomitant Candida infection may play a significant role in the pathogenesis and virulence of L. monocytogenes .